Entangled Mobilities in the Transnational Salsa Circuit : The Esperanto of the Body, Gender and Ethnicity (2020)
With attention to the transnational dance world of salsa, this book explores the circulation of people, imaginaries, dance movements, conventions and affects from a transnational perspective. Through interviews and ethnographic, multi-sited research in Havana and several European cities, the author draws on the notion of ‘entangled mobilities’ to show how the intimate gendered and ethnicized moves on the dance floor relate to the cross-border mobility of salsa dance professionals and their students. A combination of research on migration and mobility with studies of music and dance, Entangled Mobilities in the Transnational Salsa Circuit contributes to the fields of transnationalism, mobility and dance studies, thus providing a deeper theoretical and empirical understanding of gendered and racialized transnational phenomena. As such it will appeal to scholars across the social sciences with interests in migration, cultural studies and gender studies.